Photosensitive glass and its manufacturing method, tempered photosensitive glass and its use

JP7934079B2Active Publication Date: 2026-10-13CHONGQING AUREAVIA HI TECH GLASS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2026503596
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2024-08-12
Filing Date
2025-08-12
Publication Date
2026-10-13
Estimated Expiration
2045-08-12

Smart Images

  • Figure 0007934079000009
    Figure 0007934079000009
  • Figure 0007934079000010
    Figure 0007934079000010
  • Figure 0007934079000011
    Figure 0007934079000011
Patent Text Reader

Abstract

The embodiments of the present invention provide photosensitive glass and a method for producing the same, tempered photosensitive glass and their uses, and by controlling the raw material composition of the photosensitive glass, it is possible not only to ensure the stability of the glass components during the melting process of Ag2O-containing photosensitive glass, but also to generate silver atoms Ag by the decomposition of Ag2O. 0 This solves the problem of wear and tear and breakage of precious metal containers, and furthermore, when photosensitive glass is obtained after subsequent radiation and heat treatment, the optical transmittance in the visible light and near-infrared wavelength range of the exposed area is extremely low, enabling shielding against optical signals.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] [Cross-reference of related applications] This application claims priority to a Chinese patent application filed with the China National Intellectual Property Administration on August 12, 2024, with application number 202411102134.4, and titled "Photosensitive glass and its manufacturing method, tempered photosensitive glass and use," and incorporates its entire contents into this application by reference.

[0002] This invention relates to the field of glass technology, and more specifically to photosensitive glass, methods for manufacturing the same, tempered photosensitive glass, and its use. [Background technology]

[0003] Photosensitive glass can respond to external light stimuli, and under certain light irradiation conditions, its glass structure and phase change, exhibiting different mechanical and optical properties. Ag-containing photosensitive glass is the most common type of photosensitive glass, and Ag is generally combined with Ce ions and Sb ions, with Sb being present during the melting process. 3+ The electrons are Ce 4+ Transmit to Ce 3+ Reduced to Ce in subsequent UV exposure 3+ The electrons are Ag + It is transmitted to Ag 0 Reduced to Ag 0 The lattice constant is similar to that of the colloidal Ag crystal growth center, and subsequent heat treatment can lead to the precipitation and growth of Ag colloid. Due to the similar lattice constant, the Ag colloid crystal can induce the precipitation of lithium metasilicate crystals. Based on the above reaction chain principle, Corning and Schott have developed Fotoform / Fotoceram and Foturan products, respectively. Subsequent etching of the glass enables the machining of microscopic areas of the glass, which are used in MEMS, TGV, and microfluidic glass chips.

[0004] Ag-containing photosensitive glass has many problems in the melting process. For example, when containers made of corundum and quartz are used, they will significantly affect the final glass composition during the high-temperature melting process, and the melting containers are prone to rupture. When precious metal containers (especially metal containers made of platinum, rhodium, etc.) are used, Ag in the glass composition will cause corrosion to the containers, and long-term melting will cause serious wear and damage to the containers (the melting containers include crucibles, furnaces, channels, etc.). Therefore, ensuring the melting stability, maintaining the stability of the glass composition, and reducing and avoiding damage to the containers caused by the melting process are technical problems to be solved urgently.

[0005] This type of photosensitive glass is mainly applied in the field of glass micromachining, and its application in the optical field has not been reported. In fact, in the UV exposure region, the optical transmittance of the photosensitive glass decreases significantly with the precipitation of colloidal Ag crystals and the precipitation of lithium silicate crystals. This property enables Ag photosensitive glass ceramics to be applied to the shielding of optical signals, and the shielding of optical signals in a specific wavelength range in a specific region can be realized by a process combining a photomask and UV exposure for the specific region.

[0006] It should be noted that the content in this part of the present invention only provides background technology related to the present invention, and does not necessarily constitute prior art or publicly known technology. SUMMARY OF THE INVENTION

[0007] The object of the present invention is to not only realize the assurance of the stability of the glass composition during the melting process of Ag₂O-containing photosensitive glass, but also solve the problem of wear and damage of precious metal containers caused by silver atoms Ag generated by the decomposition of Ag₂O, and further, when the photosensitive glass is obtained after subsequent radiation treatment and heat treatment, the optical transmittance in the visible light and near-infrared wavelength range of its exposed region is extremely low, so as to provide a photosensitive glass capable of realizing shielding of optical signals. 0

[0008] ​To achieve the above objective, the present invention provides the following technical solutions.

[0009] According to the first embodiment, a photosensitive glass is provided, in which the mass content of each component of the raw materials in the photosensitive glass is as follows: 50 wt% to 60 wt% silica sand, 15 wt% to 22 wt% lithium carbonate, 6 wt% to 10 wt% aluminum hydroxide, 3 wt% to 6 wt% potassium nitrate, 3 wt% to 6 wt% sodium nitrate, 3 wt% to 5 wt% zirconium oxide, 0.3 wt% to 0.6 wt% silver nitrate, 0.05 wt% to 0.10 wt% cerium oxide, and pentavalent antimony salt, with sodium antimonate as the base, and the mass percentage of pentavalent antimony salt in the composition of the photosensitive glass is 0.3 wt% to 0.8 wt%.

[0010] Selectively, the photosensitive glass contains the following components, based on the mass content of each component of the raw materials:

[0011] The silica sand content is 53 wt% to 59 wt%, preferably 54.00 wt% to 58.96 wt%, and / or The lithium carbonate content is 17 wt% to 20 wt%, preferably 17.43 wt% to 19.94 wt%, and / or The aluminum hydroxide content is 8 wt% to 10 wt%, preferably 8.22 wt% to 9.97 wt%, and / or The potassium nitrate content is 4 wt% to 6 wt%, preferably 4.07 wt% to 5.97 wt%, and / or The sodium nitrate content is 3.5 wt% to 5.5 wt%, preferably 3.77 wt% to 5.45 wt%, and / or The zirconium oxide content is 3.33 wt% to 5 wt%, preferably 3.33 wt% to 4.96 wt%, and / or The silver nitrate content is 0.3 wt% to 0.5 wt%, preferably 0.32 wt% to 0.49 wt%, and / or The cerium oxide content is 0.05 wt% to 0.09 wt%, preferably 0.06 wt% to 0.09 wt%, and / or The pentavalent antimony salt content is 0.3 wt% to 0.7 wt%, preferably 0.3 wt% to 0.5 wt%.

[0012] Selectively, the pentavalent antimony salt includes at least one of NaSbO3, KSbO3, NH4SbO3, and their hydrates.

[0013] Selectively, the thickness of the photosensitive glass is 0.4 to 2.0 mm.

[0014] Selectively, the photosensitive glass has an exposed area and a non-exposed area. If the photosensitive glass thickness is 0.40 mm to 1.00 mm, the transmittance T1 at a wavelength of 850 nm in the exposed area of ​​the photosensitive glass is 0.00% to 5.00%, preferably 0.00% to 3%, and / or if the photosensitive glass thickness is 0.40 mm to 1.00 mm, the transmittance T2 at a wavelength of 550 nm in the exposed area of ​​the photosensitive glass is 0.00% to 5.00%, preferably 0.00% to 2%, and / or if the photosensitive glass thickness is 0.40 mm to 1.00 mm, the transmittance T3 at a wavelength of 850 nm in the unexposed area of ​​the photosensitive glass is 90% or more, and / or if the photosensitive glass thickness is 0.40 mm to 1.00 mm, the transmittance T4 at a wavelength of 550 nm in the unexposed area of ​​the photosensitive glass is 90% or more.

[0015] According to the second aspect, a method for manufacturing the above-mentioned photosensitive glass is provided, which includes the following steps. After preparing each component of the raw material, mixing and melting them in a noble metal container, followed by forming, and then performing an annealing treatment to obtain a base glass; The base glass includes a first region and a second region, where a masking treatment is performed on the first region, no masking treatment is performed on the second region, so as to obtain the masked base glass; After subjecting the masked base glass to irradiation treatment and heat treatment, a photosensitive glass having a non-exposed region and an exposed region is obtained, wherein the non-exposed region corresponds to the first region, and the exposed region corresponds to the second region.

[0016] Optionally, the noble metal container is a container made of a metal comprising at least one of gold, platinum, and rhodium.

[0017] Optionally, the melting temperature is 1400°C to 1650°C, and the melting time is 6h to 48h.

[0018] Optionally, the annealing temperature is 400°C to 500°C, and the annealing time is 8h to 24h.

[0019] Optionally, the masking treatment comprises masking using a masking ink and / or a photomask.

[0020] Optionally, the manner of the irradiation treatment includes ultraviolet irradiation treatment.

[0021] Optionally, the wavelength of the ultraviolet irradiation treatment is 300nm to 320nm, and the intensity of the ultraviolet irradiation treatment is 20mW / cm 2 ~360mW / cm 2 , and the time of the ultraviolet irradiation treatment is 5min to 60min.

[0022] Optionally, the heat treatment includes a nuclearization treatment and a crystallization treatment.

[0023] Selectively, the heating rate of the nucleation process is 1°C / min to 10°C / min, and / or The nucleation process temperature is 430°C to 540°C, and / or The nucleation process time is 30 min to 360 min, and / or The heating rate for the crystallization process is 1°C / min to 10°C / min, and / or The crystallization treatment temperature is 540°C to 800°C, and / or The crystallization process takes between 30 and 480 minutes.

[0024] Selectively, the thickness of the base glass is 0.4 to 2.0 mm.

[0025] According to a third embodiment, a tempered photosensitive glass is provided, the tempered photosensitive glass having a thickness of t, comprising a strengthening layer and a tensile stress layer, wherein the strengthening layer extends inward from the surface of the tempered photosensitive glass, and the thickness of the strengthening layer is 0 to 0.22t.

[0026] In the tensile stress layer and / or the center of the tempered photosensitive glass, the following components are present in terms of mass percentage of oxide: It contains SiO2: 65%~74.00%, Al2O3: 5.00%~10.00%, Li2O: 7.90%~12.00%, Na2O: 1.00%~3.00%, K2O: 1.50%~3.80%, ZrO2: 3.5%~6.50%, Ag2O: 0.20%~0.50%, CeO2: 0.07%~0.13%, and Sb2O3: 0.2%~0.50%. The reinforced layer consists of the following components by mass percentage of oxides: It contains SiO2: 65%~74.00%, Al2O3: 5.00%~10.00%, Na2O: 4.00%~16.00%, K2O: 2.0%~5.0%, ZrO2: 3.5%~6.50%, Ag2O: 0.20%~0.50%, CeO2: 0.07%~0.13%, and Sb2O3: 0.2%~0.50%, and the Li2O content in the reinforcing layer is lower than the Li2O content in the tensile stress layer and / or the center of the reinforcing photosensitive glass. Na2O is obtained from sodium nitrate. K2O can be obtained from potassium nitrate. Ag2O can be obtained from silver nitrate. Sb2O3 can be obtained using pentavalent antimony salts. The reinforced photosensitive glass includes a non-exposure area and an exposure area.

[0027] Selectively, t is between 0.4 and 2.0 mm.

[0028] Selectively, the static pressure strength of a single rod of reinforced photosensitive glass is 200 N or more, preferably 200 N to 500 N, and more preferably 200 N to 490 N.

[0029] According to the fourth embodiment, a cover glass is provided, the cover glass being made of photosensitive glass according to any one of the implementations of the first embodiment, photosensitive glass manufactured by a method for manufacturing photosensitive glass according to any one of the implementations of the second embodiment, or tempered photosensitive glass according to any one of the implementations of the third embodiment.

[0030] According to the fifth embodiment, an electronic device is provided, the electronic device including a photosensitive glass relating to any one of the implementations of the first embodiment, a photosensitive glass manufactured by a method for manufacturing photosensitive glass relating to any one of the implementations of the second embodiment, or a tempered photosensitive glass relating to any one of the implementations of the third embodiment.

[0031] Selectively, the electronic device includes a case having a top portion and a bottom portion, the bottom portion of which the case includes photosensitive glass according to any one of the embodiments of the first embodiment, photosensitive glass manufactured by a method for manufacturing photosensitive glass according to any one of the embodiments of the second embodiment, or tempered photosensitive glass according to the third embodiment.

[0032] Selectively, the electronic device further includes a camera assembly, the housing of the electronic device includes a camera protective cover, the camera protective cover is provided to cover the camera assembly, and the camera protective cover includes photosensitive glass according to any one of the embodiments of the first embodiment, or photosensitive glass manufactured by a method for manufacturing photosensitive glass according to any one of the embodiments of the second embodiment, or tempered photosensitive glass according to the third embodiment.

[0033] According to the sixth embodiment, the use of photosensitive glass according to any one of the implementations of the first embodiment, photosensitive glass manufactured by a method for manufacturing photosensitive glass according to any one of the implementations of the second embodiment, or tempered photosensitive glass according to any one of the implementations of the third embodiment is provided for the manufacture of mobile phones, smartwatches, wearable devices, camera modules, and vehicle parts.

[0034] One or more of the above-mentioned technical solutions provided by the present invention have the following advantages compared to the prior art. By controlling the raw material composition of photosensitive glass, it is possible to ensure the stability of the glass components during the melting process of Ag2O-containing photosensitive glass, and the silver atoms Ag produced by the decomposition of Ag2O. 0 This solves the problem of wear and tear and breakage of precious metal containers, and furthermore, when photosensitive glass is obtained after subsequent radiation and heat treatment, the optical transmittance in the visible light and near-infrared wavelength range of the exposed area is extremely low, enabling shielding against optical signals.

[0035] To more clearly explain the technical concepts of the embodiments of the present invention, the following briefly introduces the drawings necessary for the embodiments. Since the following drawings show only a few embodiments of the present invention, they should not be considered to limit the scope of the claims of the present invention, and those skilled in the art should understand that other relevant drawings can be obtained based on these drawings without requiring any creative effort. [Brief explanation of the drawing]

[0036] [Figure 1]Figure 1 is a schematic diagram of the structure of a substrate glass after masking using masking ink, according to an implementation embodiment of the present invention. [Figure 2] Figure 2 is a schematic diagram of the configuration of the photosensitive glass according to the present invention. [Figure 3] Figure 3 is a schematic diagram of the configuration when the electronic device according to the implementation form of the present invention is a mobile phone. [Figure 4] Figure 4 is a schematic diagram of the configuration when the electronic device according to the implementation form of the present invention is a smartwatch. [Figure 5] Figure 5 shows photographs of the inside of the crucibles after melting for Examples 9-10 and Comparative Examples 1-2 of the present invention. Figure 5a is a photograph of the bottom of the crucible for Comparative Example 1, Figure 5b is a photograph of the bottom of the crucible for Comparative Example 2, Figure 5c is a photograph of the bottom of the crucible for Example 9, and Figure 5d is a photograph of the bottom of the crucible for Example 10. [Figure 6] Figure 6 shows actual diagrams of the shielding in the visible light range of the exposure area in Examples 9-10 and Comparative Examples 1-3 of the present invention, where red light is transmitted through the bright spots in Comparative Examples 1-3. [Modes for carrying out the invention]

[0037] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art should understand that the following examples are merely illustrative and do not limit the scope of the claims. Unless otherwise specified in the examples, the procedures are carried out under normal conditions or conditions recommended by the manufacturer. Unless otherwise specified, the reagents or equipment used are all commercially available, standard products.

[0038] The endpoints and any values ​​of the ranges disclosed herein are not limited to these exact ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the intervals between the endpoint values ​​of each range, between the endpoint values ​​of each range and individual point values, and between individual point values ​​can be combined to obtain one or more new numerical ranges, and these numerical ranges should be considered specifically disclosed herein. Here, the terms “optionally” and “any” mean “optional” or “optional.” “And / or” in this specification is inclusive; for example, “A and / or B” means A only, or B only, or both A and B.

[0039] Explanation of terms and measurement methods: In this invention, the main surface refers to the surface with the largest surface area, for example, the upper or lower surface of a horizontally placed substrate glass.

[0040] In this invention, light of a certain wavelength is irradiated onto the main surface of a photosensitive glass, and the light is reflected, absorbed, and transmitted. The ratio of the intensity of the transmitted portion to the intensity of the incident light is the transmittance.

[0041] In this invention, the thickness of the glass is measured using a micrometer.

[0042] In this invention, the dimensional specifications of the glass pieces are measured using a two-dimensional measuring machine (machine model number MiyuMY~YXCL~4030).

[0043] Main surface Ag / Ag2O concentration measurement In this invention, the surface Ag / Ag2O concentration of the photosensitive glass is measured by an X-ray fluorescence spectrometer (XRF), and the instrument used for measurement is Thermo Scientific ARL® PERFORM'X. The target material is Rh (rhodium), the photocell voltage is 40KW, the current is 60mA, the collimator is 0.15, LiF200 crystal is selected, the detector is FPC, the measurement range is a 29mm circle, and the analysis software is Standardless UniQuant. No standard material is used during XRF measurement, and the concentration of elements with atomic numbers of 6 or less or their oxides in the glass is not measured. Specifically, for example, SiO2, Al2O3, Na2O, K2O, etc. can be measured accurately, but Li2O, B2O3, etc. cannot be measured accurately. That is, in this invention, when the surface Ag / Ag2O concentration is measured by XRF, the total mass of surface elements or their oxides does not include the mass of elements with atomic numbers of 6 or less or their oxides in the glass.

[0044] In this invention, the transmittance of the exposed and unexposed regions of a glass object to be measured is measured using an ultraviolet-visible spectrophotometer. The ultraviolet-visible spectrophotometer used for the measurement in this invention is a UV~2000 ultraviolet-visible spectrophotometer manufactured by Shimadzu Corporation.

[0045] The method for measuring the exposed area of ​​the glass to be measured is as follows: First, a jig is used as a blank sample for test calibration. The jig has a shape and size that matches the glass to be measured, and the same area corresponding to the exposed area of ​​the glass to be measured is a hollow area, and the area corresponding to the unexposed area of ​​the glass to be measured is an opaque area, and the connection position between the hollow area and the opaque area is determined by opaque jig. After that, the exposed area of ​​the glass to be measured is cut into a sample that overlaps with the shape of the hollow area of ​​the jig, and the transmittance is obtained by placing it in the hollow area of ​​the jig and measuring it. Using an ultraviolet-visible spectrophotometer, the transmittance of the exposed area of ​​five pieces of the glass to be measured for different wavelengths of light is measured, and then the average value is taken as the result of the transmittance of the exposed area of ​​the glass to be measured for that wavelength of light.

[0046] Furthermore, using a UV-Vis spectrophotometer, the transmittance of the unexposed areas of five glass samples from the same batch to different wavelengths of light is measured. The average value of the transmittances measured at different wavelengths in the unexposed areas of the five glass samples is taken and used as the result for the transmittance of the unexposed area of ​​the glass sample at that wavelength.

[0047] In this invention, the measurement of single-rod static pressure strength may be carried out as follows: Place the glass sample to be measured in the bottom ring of the tensile testing machine (LT-850A), start the measurement software, set the movement speed of the pressing rod (rod diameter 8 mm, indenter arc radius 10 mm) to 50 mm / min, click Start Measurement, and apply force to the center of the glass sample at the set movement speed with the pressing rod until a crack occurs in the glass sample and it breaks. The measurement software automatically reads the force (N) at which the glass sample breaks as the measurement result. Take 10 glass samples in the same condition and perform the measurement, and the average value of the measurement results is taken as the single-rod static pressure strength of the glass sample to be measured.

[0048] In this invention, the wavelength range of visible light and near-infrared light refers to 400 nm to 1000 nm.

[0049] In the present invention, the glass component contains Ag2O and undergoes the following reversible reaction during the melting process.

[0050]

number

[0051] Decomposition causes silver atoms (Ag) 0 Therefore, Ag is produced by the decomposition of Ag2O. 0 To prevent corrosion and damage to the precious metal container of the mixed molten raw materials, the present invention uses various other raw material components that can provide an oxygen gas atmosphere other than Ag2O to perform the melting process, and Ag2O is converted to Ag 0This suppresses the conversion to [a specific type of substance]. Preferably, the raw material components that can provide an oxygen gas atmosphere include nitrates and pentavalent antimony salts, and specifically, nitrates containing NaNO3, KNO3, AgNO3, etc. are used as raw material components. The nitrates decompose in the melting process to produce O2, and the specific reaction is as follows. Furthermore, an oxidizing atmosphere can be provided to suppress the decomposition of Ag2O.

[0052]

number

[0053] Furthermore, pentavalent antimony salts containing NaSbO3, KSbO3, NH4SbO3, and their hydrates can decompose during the melting process to generate an oxygen gas atmosphere, and Ag2O can also be converted into Ag 0 This inhibits the conversion to [a specific substance]. Using NaSbO3 as an example, the specific reaction is as follows:

[0054]

number

[0055] Also, Sb 5+ Sb produced when antimony salt decomposes during the melting process. 3+ As a reducing agent, Ce in glass 4+ to Ce 3+ Reduce to Ce 3+ The effective content can be maintained, and furthermore, the exposure area of ​​the photosensitive glass is, in the later stages, under radiation conditions, for example, under ultraviolet irradiation, Ce 3+ Ag + to Ag 0 It can be reduced to Ag 0 The growth center is used, and then Ag is produced by heat treatment. 0 The clusters can generate crystal nuclei, inducing the precipitation of lithium metasilicate crystals.

[0056] This invention ensures stability during the melting process of Ag2O-containing photosensitive glass by controlling the composition of the photosensitive glass, and Ag0 It does not produce Ag, and furthermore, Ag produced by Ag2O decomposition 0 This solves the problem of corrosion and damage to containers made of molten precious metals. Furthermore, after radiation and heat treatment, the exposed area of ​​the photosensitive glass forms an opaque area, ensuring that optical signals in the visible and near-infrared wavelength ranges are shielded.

[0057] In some embodiments of the present invention, a photosensitive glass is provided, comprising, in terms of the mass content of each component of the raw materials in the photosensitive glass, 50 wt% to 60 wt% silica sand, 15 wt% to 22 wt% lithium carbonate, 6 wt% to 10 wt% aluminum hydroxide, 3 wt% to 6 wt% potassium nitrate, 3 wt% to 6 wt% sodium nitrate, 3 wt% to 5 wt% zirconium oxide, 0.3 wt% to 0.6 wt% silver nitrate, 0.05 wt% to 0.10 wt% cerium oxide, and a pentavalent antimony salt, wherein, based on sodium antimonate, the mass percentage of the pentavalent antimony salt in the photosensitive glass is 0.3 wt% to 0.8 wt%.

[0058] The type of crystal that precipitates in the crystallization process of photosensitive glass is mainly lithium metasilicate (Li2SiO3). The precipitation of Li2SiO3 is advantageous in reducing the optical transmittance of the exposed area of ​​the photosensitive glass, and is advantageous in that the photosensitive glass can shield optical signals in the visible light and near-infrared wavelength ranges. In the present invention, SiO2 is a glass-forming oxide that serves as the network framework of the glass derived from silica sand. In some embodiments of the present invention, the silica sand content in the photosensitive glass is 53 wt% to 60 wt%, preferably 53 wt% to 59 wt%, and more preferably 54.00 wt% to 58.96 wt% by mass of each component of the raw materials.

[0059] In some embodiments of the present invention, the mass content of silica sand in the photosensitive glass, as expressed by the mass content of each component of the raw materials, may be 53 wt%, 53.5 wt%, 54 wt%, 54.5 wt%, 55 wt%, 55.5 wt%, 56 wt%, 56.5 wt%, 57 wt%, 57.5 wt%, 58 wt%, 58.5 wt%, 58.96 wt%, 59 wt%, or 60 wt%, or it may be a value within a numerical range formed with any two of the above specific values ​​as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other ranges.

[0060] In some embodiments of the present invention, the mass percentage of lithium carbonate in the photosensitive glass, based on the mass content of each component of the raw materials, is 15 wt% to 22 wt%, preferably 15 wt% to 20 wt%, and more preferably 17 wt% to 20 wt%. In some embodiments of the present invention, the lithium carbonate content in the photosensitive glass, based on the mass content of each component of the raw materials, may be 15 wt%, 16 wt%, 17 wt%, 17.43 wt%, 17.5 wt%, 18 wt%, 18.5 wt%, 19 wt%, 19.5 wt%, 19.94 wt%, 20 wt%, 21 wt%, or 22 wt%, or it may be a number within a numerical range formed with any two of the above specific numerical values ​​as endpoints. It should be understood that in the implementation, any of the above ranges can be combined with any other ranges.

[0061] In the present invention, Al2O3 enters the glass network structure as an intermediate in the glass network in the form of an [AlO4] tetrahedron, and aluminum oxide is derived from aluminum hydroxide, which can improve the stability of the photosensitive glass. In some embodiments of the present invention, the mass content of aluminum hydroxide in the photosensitive glass of each component of the raw materials is 6 wt% to 10 wt%, preferably 8 wt% to 10 wt%, and more preferably 8.22 wt% to 9.97 wt%. In some embodiments of the present invention, the mass content of aluminum hydroxide in the photosensitive glass of each component of the raw materials may be 6 wt%, 7 wt%, 8 wt%, 8.22 wt%, 8.5 wt%, 8.7 wt%, 9 wt%, 9.2 wt%, 9.5 wt%, 9.7 wt%, 9.97 wt%, or 10 wt%, or it may be a value within a numerical range formed with any two of the above specific values ​​as endpoints. Please understand that in this implementation plan, any of the above ranges can be combined with any other ranges.

[0062] In the present invention, zirconium oxide (ZrO2) can improve the chemical stability of photosensitive glass. However, because ZrO2 has a high melting point, if too much is added, the melting temperature of the photosensitive glass will rise. In some embodiments of the present invention, the zirconium oxide content in the photosensitive glass, in terms of the mass content of each component of the raw materials, is 3 wt% to 5 wt%, preferably 3.33 wt% to 5 wt%, and more preferably 3.33 wt% to 4.96 wt%. In some embodiments of the present invention, the zirconium oxide content in the photosensitive glass, as expressed by the mass content of each component of the raw materials, may be 3.0 wt%, 3.2 wt%, 3.33 wt%, 3.5 wt%, 3.7 wt%, 4.0 wt%, 4.2 wt%, 4.5 wt%, 4.8 wt%, 4.96 wt%, or 5.0 wt%, or it may be a value within a numerical range formed with any two of the above specific values ​​as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other ranges.

[0063] In this invention, Na2O and K2O are glass network modifying oxides, fluxes, and can lower the melting temperature of glass. + , K + If Na + , K + The lithium preferentially enters the aluminum-silicon network to compensate for the charge, maintains a certain level of lithium content in the lithium-rich region, and brings the Si / Li ratio in the lithium-rich region closer to the chemical ratio of Li2SiO3. This demonstrated that the precipitated crystalline phase of the photosensitive glass containing Na2O and K2O is lithium metasilicate. Na2O is derived from sodium nitrate, and K2O is derived from potassium nitrate. In this invention, nitrates such as sodium nitrate, potassium nitrate, and silver nitrate, when combined with antimonate salts, provide a better clarification effect and further affect the performance of the finished product, such as transmittance, while carbonates cannot achieve the transmittance effect of the finished product according to this invention.

[0064] In some embodiments of the present invention, the mass content of sodium nitrate in the photosensitive glass of each component of the raw materials is 3.0 to 6.0 wt%, preferably 3.5 to 5.5 wt%, and more preferably 3.77 wt% to 5.45 wt%. In some embodiments of the present invention, the mass content of sodium nitrate in the photosensitive glass of each component of the raw materials may be 3.0 wt%, 3.5 wt%, 3.77 wt%, 4.0 wt%, 4.2 wt%, 4.5 wt%, 4.8 wt%, 5 wt%, 5.3 wt%, 5.45 wt%, or 5.5 wt%, or a number within a numerical range formed with any two of the above specific values ​​as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other ranges.

[0065] In some embodiments of the present invention, the mass content of potassium nitrate in the photosensitive glass of each component of the raw materials is 3 wt% to 6 wt%, preferably 4 wt% to 6 wt%, and more preferably 4.07 wt% to 5.97 wt%. In some embodiments of the present invention, the mass content of potassium nitrate in the photosensitive glass of each component of the raw materials may be 3.0 wt%, 4.0 wt%, 4.07 wt%, 4.2 wt%, 4.5 wt%, 4.7 wt%, 5.0 wt%, 5.2 wt%, 5.5 wt%, 5.8 wt%, 5.97 wt%, or 6.0 wt%, or a number within a numerical range formed with any two of the above specific values ​​as endpoints. It should be understood that in the implementation, any of the above ranges can be combined with any other range.

[0066] In some embodiments of the present invention, the mass content of silver nitrate in the photosensitive glass of each component of the raw materials is 0.3 wt% to 0.6 wt%, preferably 0.30 wt% to 0.5 wt%, more preferably 0.32 wt% to 0.49 wt%, and in some embodiments of the present invention, the mass content of silver nitrate in the photosensitive glass of each component of the raw materials may be 0.30 wt%, 0.32 wt%, 0.35 wt%, 0.37 wt%, 0.40 wt%, 0.43 wt%, 0.45 wt%, 0.49 wt%, 0.50 wt%, or 0.60 wt%, or a number within a numerical range formed with any two of the above specific numerical values ​​as endpoints. It should be understood that in the implementation, any of the above ranges can be combined with any other ranges.

[0067] Cerium oxide (CeO2) is a photosensitizer, and in the UV exposure process, Ag +This provides electrons. In some embodiments of the present invention, the mass content of cerium oxide in the photosensitive glass of each component of the raw materials is 0.05 wt% to 0.10 wt%, preferably 0.05 wt% to 0.09 wt%, and more preferably 0.06 wt% to 0.09 wt%. In some embodiments of the present invention, the mass content of cerium oxide in the photosensitive glass of each component of the raw materials may be 0.05 wt%, 0.06 wt%, 0.07 wt%, 0.08 wt%, 0.09 wt%, or 0.10 wt%, or a number within a numerical range formed with any two of the above specific numerical values ​​as endpoints. It should be understood that in the implementation, any of the above ranges can be combined with any other ranges.

[0068] In some embodiments of the present invention, Sb 5+ To ensure that the amount is sufficient, in the present invention, the content of pentavalent antimony salt in the photosensitive glass of each component of the raw materials, based on sodium antimonate, is 0.3 wt% to 0.8 wt%, preferably 0.31 wt% to 0.5 wt%, and more preferably 0.31 wt% to 0.49 wt%.

[0069] In some embodiments of the present invention, the content of pentavalent antimony salt in the photosensitive glass, based on sodium antimonate, may be 0.30 wt%, 0.31 wt%, 0.33 wt%, 0.35 wt%, 0.38 wt%, 0.40 wt%, 0.43 wt%, 0.45 wt%, 0.48 wt%, 0.49 wt%, or 0.50 wt%, or it may be a value within a numerical range formed with any two of the above specific values ​​as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other ranges.

[0070] Note that pentavalent antimony salts include, but are not limited to, sodium antimonate, potassium antimonate, ammonium antimonate, and / or hydrates thereof. In this invention, different types of pentavalent antimony salts are all calculated using sodium antimonate.

[0071] In some embodiments of the present invention, the pentavalent antimony salt comprises at least one of NaSbO3, KSbO3, NH4SbO3, and their hydrates.

[0072] In the present invention, the photosensitive glass includes an exposed region and a non-exposed region, the exposed region having low transmittance in the visible light and near-infrared wavelength range, and the non-exposed region having high transmittance in the visible light and near-infrared wavelength range. In some embodiments of the present invention, when the thickness of the photosensitive glass is 0.40 mm to 1.00 mm, the transmittance T1 at a wavelength of 850 nm in the exposed region of the photosensitive glass is 0.00% to 5.00%, preferably 0.00% to 3%. In some embodiments of the present invention, when the thickness of the photosensitive glass is 0.40 mm to 1.00 mm, the transmittance T1 at a wavelength of 850 nm in the exposure region of the photosensitive glass may be 0.00%, 0.22%, 0.50%, 0.88%, 0.96%, 1.00%, 1.27%, 1.55%, 1.59%, 1.64%, 2.00%, 2.30%, 2.51%, 3.00%, 3.50%, 4.00%, 4.50%, 4.80%, or 5.00%, or a number within a numerical range formed with any two of the above specific numerical values ​​as endpoints. It should be understood that in the implementation, any of the above ranges can be combined with any other range.

[0073] In some embodiments of the present invention, when the thickness of the photosensitive glass is 0.40 mm to 1.00 mm, the transmittance T2 at a wavelength of 550 nm in the exposure region of the photosensitive glass is 0.00% to 5.00%, preferably 0.00% to 2%. In some embodiments of the present invention, when the thickness of the photosensitive glass is 0.40 mm to 1.00 mm, the transmittance T2 at a wavelength of 550 nm in the exposure region of the photosensitive glass may be 0.00%, 0.20%, 0.50%, 0.70%, 0.90%, 1.00%, 1.35%, 1.50%, 1.70%, 2.00%, 2.50%, 3.00%, 3.50%, 4.00%, 4.20%, 4.50%, 4.90%, or 5.00%, or it may be a number within a numerical range formed with any two of the above specific numerical values ​​as endpoints. Please understand that in this implementation plan, any of the above ranges can be combined with any other ranges.

[0074] In some embodiments of the present invention, when the thickness of the photosensitive glass is 0.40 mm to 1.00 mm, the transmittance T3 at a wavelength of 850 nm in the unexposed region of the photosensitive glass is 90% or more. In some embodiments of the present invention, when the thickness of the photosensitive glass is 0.40 mm to 1.00 mm, the transmittance T3 at a wavelength of 850 nm in the unexposed region of the photosensitive glass may be 90.00%, 90.50%, 91.00%, 91.69%, 91.92%, 92.03%, 92.21%, 93.00%, 93.50%, 94.00%, 94.80%, or 95.00%, or it may be a number within a numerical range formed with any two of the above specific numerical values ​​as endpoints. It should be understood that in the implementation, any of the above ranges can be combined with any other ranges.

[0075] In some embodiments of the present invention, when the thickness of the photosensitive glass is 0.40 to 1.00 mm, the transmittance T4 at a wavelength of 550 nm in the non-exposed region of the photosensitive glass is 90% or more. In some embodiments of the present invention, when the thickness of the photosensitive glass is 0.40 to 1.00 mm, the transmittance T4 at a wavelength of 550 nm in the non-exposed region of the photosensitive glass may be 90.00%, 90.74%, 91.05%, 91.60%, 92.03%, 92.50%, 93.00%, 93.50%, 94.00%, 94.80%, or 95.00%, or it may be a number within a numerical range formed with any two of the above specific numerical values ​​as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other ranges.

[0076] In some embodiments of the present invention, a method for manufacturing the above-mentioned photosensitive glass is provided, and this method is After preparing each component of the raw materials, they are mixed and melted in a precious metal container, then molded, and then annealed to obtain a base glass. The substrate glass includes a first region and a second region. The first region is masked, while the second region is not masked, in order to obtain the masked substrate glass. The method includes performing radiation treatment and heat treatment on a masked substrate glass to obtain a photosensitive glass having a non-exposed region and an exposed region, wherein the non-exposed region corresponds to a first region and the exposed region corresponds to a second region.

[0077] In the present invention, the container includes, but is not limited to, crucibles, furnaces, channels, etc., and here, a container made of precious metal means that at least the part that comes into contact with the raw materials is made of precious metal, and precious metals include, but are not limited to, gold, platinum, rhodium, etc. In some embodiments of the present invention, the container made of precious metal is a container made of a metal containing at least one of gold, platinum, and rhodium.

[0078] In the present invention, the base glass can be manufactured using conventional molding methods, and the present invention does not limit this in any way. For example, the molding method for the base glass may include, but is not limited to, the float method, overflow method, stretching method, rolling method, or casting method.

[0079] For example, a limited amount of raw materials and their corresponding weights can be used for compounding. After the raw materials are uniformly mixed, they can be sequentially poured into precious metal containers and melted, with the pouring method adjusted according to the type of precious metal container. After the glass melting is complete, it is molded to form a glass block. The glass block is then transferred to an annealing furnace for annealing, and after annealing is complete, it is allowed to cool naturally to room temperature to obtain the base glass.

[0080] In some embodiments of the present invention, the composition of the substrate glass of the present invention is the same as or substantially the same as the composition of the photosensitive glass, and its specific composition is as described above.

[0081] In some embodiments of the present invention, the melting temperature is 1400°C to 1650°C, and the melting time is 6 hours to 48 hours. In some embodiments of the present invention, the melting temperature may be 1400°C, 1475°C, 1500°C, 1525°C, 1550°C, 1575°C, 1600°C, 1625°C, or 1650°C, or a number within a numerical range formed with any two of the above specific numerical values ​​as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other ranges.

[0082] In some embodiments of the present invention, the melting time may be any one of the following values: 6h, 9h, 12h, 15h, 18h, 21h, 24h, 27h, 30h, 33h, 36h, 39h, 42h, 45h, 48h, or any value within a numerical range formed with any two of the above specific numerical values ​​as endpoints. It should be understood that in certain embodiments, any of the above ranges may be combined with any other ranges, as long as a photosensitive glass having the desired properties of the present invention is obtained.

[0083] In some embodiments of the present invention, the annealing temperature is 400°C to 500°C, and the annealing time is 8 hours to 24 hours. In some embodiments of the present invention, the annealing temperature is 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, or 500°C, or a number within a numerical range formed with any two of the above specific numbers as endpoints. It should be understood that in the implementation, any of the above ranges can be combined with any other ranges.

[0084] In some embodiments of the present invention, the annealing time may be 5h, 6h, 7h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, or 24h, or any number within a numerical range formed with any two of the above specific numerical values ​​as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other ranges.

[0085] In some embodiments of the present invention, the masking process includes masking using masking ink and / or a photomask.

[0086] For example, a schematic diagram of the substrate glass structure after masking with masking ink is shown in Figure 1, where the composite circular hole has a light-transmitting region 11 with an inner diameter and a light-shielding region 12 other than the inner diameter. A schematic diagram of the correspondingly formed photosensitive glass structure is shown in Figure 2, where an exposure region 21 is formed at the position corresponding to the light-transmitting region 11, and a non-exposure region 22 is formed at the position corresponding to the light-shielding region 12.

[0087] In some embodiments of the present invention, the radiation treatment method includes ultraviolet irradiation treatment.

[0088] In some embodiments of the present invention, the wavelength of the ultraviolet irradiation treatment is 300 nm to 320 nm, and the intensity of the ultraviolet irradiation treatment is 20 mW / cm². 2 ~360mW / cm 2The UV irradiation treatment time is 5 min to 60 min.

[0089] In some embodiments of the present invention, the wavelength of the ultraviolet irradiation treatment is 300 nm, 302 nm, 305 nm, 308 nm, 310 nm, 312 nm, 315 nm, 317 nm, or 320 nm, or a numerical value within a range defined by any two of the above specific values ​​as endpoints. In some embodiments of the present invention, the intensity of the ultraviolet irradiation treatment is 20 mW / cm². 2 40 mW / cm² 2 60mW / cm² 2 80mW / cm² 2 , 100mW / cm 2 , 120mW / cm 2 , 140mW / cm 2 , 160mW / cm 2 , 180mW / cm 2 , 200mW / cm 2 , 210 mW / cm 2 , 220mW / cm 2 , 230mW / cm 2 , 240mW / cm 2 , 250mW / cm 2 260mW / cm² 2 , 270mW / cm 2 , 280mW / cm 2 290 mW / cm² 2 , 300mW / cm 2 310 mW / cm² 2 , 320mW / cm 2 330mW / cm² 2 340mW / cm² 2 350mW / cm² 2 or 360 mW / cm² 2, or a number within a numerical range formed with any two of the above specific numbers as endpoints. In some embodiments of the present invention, the UV irradiation time is 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, or 60 min, or a number within a numerical range formed with any two of the above specific numbers as endpoints, as long as a photosensitive glass having the properties required for the present invention can be obtained. In certain embodiments, it should be understood that any of the above ranges can be combined with any other range, as long as a photosensitive glass having the desired properties of the present invention can be obtained.

[0090] In some embodiments of the present invention, the heat treatment includes a nucleation treatment and a crystallization treatment. The nucleation treatment and crystallization treatment may be any common process in the art.

[0091] In some embodiments of the present invention, the heating rate of the nucleation process is 1°C / min to 10°C / min. In some embodiments of the present invention, the duration of the nucleation process may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, or 10°C / min, or a value within a numerical range configured with any two of the above specific values ​​as endpoints. In some embodiments of the present invention, the temperature of the nucleation process may be 430°C to 500°C. In some embodiments of the present invention, the temperature of the nucleation process may be 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, or 500°C, or a value within a numerical range configured with any two of the above specific values ​​as endpoints. In some embodiments of the present invention, the duration of the nucleation process is 30 min to 360 min. In some embodiments of the present invention, the nucleation treatment time may be 30 min, 45 min, 50 min, 55 min, 60 min, 90 min, 100 min, 120 min, 140 min, 150 min, 160 min, 170 min, 180 min, 190 min, 200 min, 220 min, 240 min, 280 min, 300 min, 320 min, 340 min, or 360 min, or it may be a number within a numerical range formed with any two of the above specific numbers as endpoints.

[0092] In the present invention, the crystallization treatment includes a one-stage crystallization treatment and a multi-stage crystallization treatment. In some embodiments of the present invention, the heating rate of the crystallization treatment is 1°C / min to 10°C / min. In some embodiments of the present invention, the duration of the crystallization treatment may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, or 10°C / min, or it may be a number within a numerical range formed with any two of the above specific numerical values ​​as endpoints.

[0093] In some embodiments of the present invention, the temperature of the one-step crystallization treatment may be 500°C to 800°C. In some embodiments of the present invention, the temperature of the one-step crystallization treatment may be 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 600°C, 650°C, 700°C, 750°C, or 800°C, or a number within a numerical range formed with any two of the above specific numerical values ​​as endpoints. In some embodiments of the present invention, the duration of the one-step crystallization treatment is 30 min to 480 min. In some embodiments of the present invention, the crystallization treatment time may be 30 min, 45 min, 50 min, 55 min, 60 min, 90 min, 100 min, 120 min, 140 min, 150 min, 160 min, 170 min, 180 min, 190 min, 200 min, 220 min, 240 min, 280 min, 300 min, 340 min, 380 min, 400 min, 430 min, 450 min, or 480 min, or it may be a number within a numerical range formed with any two of the above specific numbers as endpoints.

[0094] In some embodiments of the present invention, the multi-stage crystallization process includes a two-stage crystallization process. In some embodiments of the present invention, the temperature of the first stage crystallization process in the two-stage crystallization process is 500°C to 560°C, and the temperature of the second stage crystallization process is 560°C to 800°C. It is understood that the temperature of the second stage crystallization process is higher than the temperature of the first stage crystallization process.

[0095] In some embodiments of the present invention, the temperature of the first crystallization stage in the two-stage crystallization process may be 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, or 560°C, or it may be a number within a numerical range formed with any two of the above specific numbers as endpoints. In some embodiments of the present invention, the temperature of the second crystallization stage in the two-stage crystallization process may be 560°C, 570°C, 580°C, 600°C, 650°C, 700°C, 750°C, or 800°C, or it may be a number within a numerical range formed with any two of the above specific numbers as endpoints.

[0096] In some embodiments of the present invention, the time for the first crystallization stage in a two-stage crystallization process is 30 min to 240 min, and the time for the second crystallization stage is 30 min to 240 min. In some embodiments of the present invention, the time for the first crystallization stage in a two-stage crystallization process may be 30 min, 45 min, 50 min, 55 min, 60 min, 90 min, 100 min, 120 min, 140 min, 150 min, 160 min, 170 min, 180 min, 190 min, 200 min, 220 min, or 240 min, or it may be a number within a numerical range configured with any two of the above specific numerical values ​​as endpoints. In some embodiments of the present invention, the duration of the second crystallization stage in the two-stage crystallization process may be 30 min, 45 min, 50 min, 55 min, 60 min, 90 min, 100 min, 120 min, 140 min, 150 min, 160 min, 170 min, 180 min, 190 min, 200 min, 220 min, or 240 min, or it may be a number within a numerical range formed with any two of the above specific numerical values ​​as endpoints.

[0097] Before and / or after heat treatment, those skilled in the art may perform other general steps to obtain a photosensitive glass sample that meets the desired specifications or requirements, such as shaping, cutting (e.g., using a multi-wire saw), CNC machining (computer numerical control, i.e., CNC machine tool), thinning, or polishing. The present invention does not limit the dimensions of the photosensitive glass, which may be, for example, 50 mm × 50 mm × 1.0 mm, 300 mm × 120 mm × 0.7 mm, etc.

[0098] In some embodiments of the present invention, the thickness of the substrate glass and / or photosensitive glass of the present invention is not particularly limited and may be, for example, 0.4 to 2.0 mm. In some embodiments of the present invention, the thickness of the photosensitive glass of the present invention may be 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm or 2.0 mm, or a number within a numerical range formed with any two of the above specific numbers as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other range.

[0099] In some embodiments of the present invention, a tempered photosensitive glass is provided, the tempered photosensitive glass having a thickness of t, comprising a strengthening layer and a tensile stress layer, wherein the strengthening layer extends inward from the surface of the tempered photosensitive glass, and the thickness of the strengthening layer is 0 to 0.22t.

[0100] In the tensile stress layer and / or the center of the tempered photosensitive glass, the following components are present in terms of mass percentage of oxide: It contains SiO2: 65%~74.00%, Al2O3: 5.00%~10.00%, Li2O: 7.90%~12.00%, Na2O: 1.00%~3.00%, K2O: 1.50%~3.80%, ZrO2: 3.5%~6.50%, Ag2O: 0.20%~0.50%, CeO2: 0.07%~0.13%, and Sb2O3: 0.2%~0.50%. The reinforced layer consists of the following components by mass percentage of oxides: It contains SiO2: 65%~74.00%, Al2O3: 5.00%~10.00%, Na2O: 4.00%~16.00%, K2O: 2.0%~5.0%, ZrO2: 3.5%~6.50%, Ag2O: 0.20%~0.50%, CeO2: 0.07%~0.13%, and Sb2O3: 0.2%~0.50%, and the Li2O content in the reinforcing layer is lower than the Li2O content in the tensile stress layer and / or the center of the reinforcing photosensitive glass. Na2O is obtained from sodium nitrate. K2O can be obtained from potassium nitrate. Ag2O can be obtained from silver nitrate. Sb2O3 can be obtained using pentavalent antimony salts. The reinforced photosensitive glass includes a non-exposure area and an exposure area.

[0101] In some embodiments of the present invention, a tempered photosensitive glass having a thickness t is provided, and the tempered photosensitive glass is obtained by chemically strengthening the photosensitive glass of any of the above embodiments.

[0102] In some embodiments of the present invention, the reinforced photosensitive glass comprises a reinforcement layer and a tensile stress layer, the reinforcement layer comprising the following components by mass percentage of oxides: The composition of each component is as follows: SiO2: 65%~74.00%, Al2O3: 5.00%~10.00%, Na2O: 4.00%~16.00%, K2O: 2.0%~5.0%, ZrO2: 3.5%~6.50%, Ag2O: 0.20%~0.50%, CeO2: 0.07%~0.13%, and Sb2O3: 0.2%~0.50%. The Li2O content in the reinforcing layer is lower than the Li2O content in the tensile stress layer and / or the center of the reinforcing photosensitive glass. Na2O is obtained from sodium nitrate. K2O can be obtained from potassium nitrate. Ag2O can be obtained from silver nitrate. Sb2O3 can be obtained using pentavalent antimony salts. In the tensile stress layer and / or the center of the tempered photosensitive glass, the following components are present in terms of mass percentage of oxide: It contains SiO2: 65%~74.00%, Al2O3: 5.00%~10.00%, Li2O: 7.90%~12.00%, Na2O: 1.00%~3.00%, K2O: 1.50%~3.80%, ZrO2: 3.5%~6.50%, Ag2O: 0.20%~0.50%, CeO2: 0.07%~0.13%, and Sb2O3: 0.2%~0.50%.

[0103] In the present invention, SiO2 is a glass-forming oxide that forms an irregular continuous network of silicon-oxygen tetrahedron structural units, forming the framework for glass. In some embodiments of the present invention, the SiO2 content in the strengthened layer, tensile stress layer, or center of the strengthened photosensitive glass is 65.00% to 74.00% by mass percentage of oxide, preferably 66.00% to 73.20%.

[0104] In some embodiments of the present invention, the SiO2 content in the strengthened layer, tensile stress layer, or core of the strengthened photosensitive glass, in terms of mass percentage of oxide, may be 65.00%, 66.00%, 67.00%, 68.00%, 69.00%, 70.00%, 71.00%, 72.00%, 73.00%, or 74.00%, or it may be a value within a range formed with any two of the above specific values ​​as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other range.

[0105] In this invention, Al2O3 is an intermediate in the glass network and enters the glass network structure as an [AlO4] tetrahedron. The increase in Al2O3 is the T of the glass. gThis is advantageous for increasing the temperature, improving thermal stability, and suppressing phase separation during the heat treatment process of glass, but if too much is used, it will increase the melting temperature of the glass. In some embodiments of the present invention, the Al2O3 content in the strengthened layer, tensile stress layer, or core of the strengthened photosensitive glass is 5.00% to 10.00% by mass percentage of oxide, preferably 5.10% to 9.70%, and more preferably 5.20% to 9.40%.

[0106] In some embodiments of the present invention, the Al2O3 content in the strengthened layer, tensile stress layer, or core of the strengthened photosensitive glass, in terms of mass percentage of oxide, may be 5.00%, 5.50%, 6.00%, 6.50%, 7.00%, 7.50%, 8.00%, 8.50%, 9.00%, 9.50%, 10.00%, 7.25%, 5.83%, 8.76%, 7.62%, 7.89%, 6.47%, or 8.96%, or any value within a range defined by any two of the above specific values ​​as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other range.

[0107] In some embodiments of the present invention, the Li2O content in the tensile stress layer or center of the tempered photosensitive glass is 7.90% to 12.00% by mass percentage of oxides.

[0108] In some embodiments of the present invention, the Li2O content in the tensile stress layer or center of the tempered photosensitive glass, by mass percentage of oxide, may be 7.90%, 8.00%, 8.50%, 9.00%, 9.50%, 10.00%, 10.50%, 11.00%, 11.50%, or 12.00%, or any value within a range defined by any two of the above specific values ​​as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other range.

[0109] In some embodiments of the present invention, the Li2O content in the reinforced layer is lower in terms of mass percentage of oxide than the Li2O content in the tensile stress layer and / or the center of the reinforced photosensitive glass.

[0110] In some embodiments of the present invention, the Na2O content in the tensile stress layer or center of the tempered photosensitive glass, by mass percentage of oxide, is 1.00% to 3.00%, preferably 1.00% to 2.80%. In some embodiments of the present invention, the Na2O content in the tensile stress layer or center of the tempered photosensitive glass, by mass percentage of oxide, may be 1.00%, 1.10%, 1.20%, 1.30%, 1.40%, 1.50%, 1.60%, 1.70%, 1.80%, 1.90%, 2.00%, 2.10%, 2.20%, 2.30%, 2.40%, 2.50%, 2.60%, 2.70%, 2.80%, 2.90%, or 3.00%, or it may be a value within a numerical range configured with any two of the above specific values ​​as endpoints. Please understand that in this implementation plan, any of the above ranges can be combined with any other ranges.

[0111] In some embodiments of the present invention, the Na2O content in the strengthening layer of the tempered photosensitive glass is 4.00% to 16.00% by mass percentage of oxides, preferably 4.00% to 15%. In some embodiments of the present invention, the Na2O content in the strengthening layer of the tempered photosensitive glass is 4.00%, 4.50%, 4.80%, 5.00%, 5.40%, 5.80%, 6.60%, 6.90%, 7.00%, 7.20%, 7.80%, 8.00%, 8.50%, 8.90%, 9.00%, 9.50%, and 10.0% by mass percentage of oxides. The ranges may be 10.30%, 10.80%, 11.00%, 11.50%, 12.00%, 12.50%, 12.90%, 13.00%, 13.50%, 14.00%, 14.50%, 15.00%, 15.60%, 15.90%, or 16.00%, or any number within a range formed with any two of the above specific values ​​as endpoints. In this implementation, it should be understood that any of the above ranges can be combined with any other range.

[0112] In some embodiments of the present invention, the K2O content in the tensile stress layer or center of the tempered photosensitive glass, by mass percentage of oxide, is 1.50% to 3.80%, preferably 1.80% to 3.50%. In some embodiments of the present invention, the K2O content in the tensile stress layer or center of the tempered photosensitive glass, by mass percentage of oxide, may be 1.50%, 1.80%, 2.00%, 2.30%, 2.40%, 2.80%, 3.00%, 3.30%, 3.40%, 3.50%, 3.60%, 3.70%, or 3.80%, or may be a number within a numerical range formed with any two of the above specific values ​​as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other ranges.

[0113] In some embodiments of the present invention, the K2O content in the tempered layer of tempered photosensitive glass, by mass percentage of oxide, is 2.00% to 5.00%, preferably 2.20% to 4.90%. In some embodiments of the present invention, the K2O content in the tempered layer of tempered photosensitive glass, by mass percentage of oxide, may be 2.00%, 2.50%, 2.80%, 3.00%, 3.40%, 3.80%, 4.00%, 4.30%, 4.80%, or 5.00%, or it may be a value within a numerical range formed with any two of the above specific values ​​as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other ranges.

[0114] In some embodiments of the present invention, the ZrO2 content in the strengthened layer, tensile stress layer, or core of the tempered photosensitive glass, by mass percentage of oxide, is 3.50% to 6.50%, preferably 3.80% to 6.40%. In some embodiments of the present invention, the ZrO2 content in the strengthened layer, tensile stress layer, or core of the tempered photosensitive glass, by mass percentage of oxide, may be 3.50%, 3.80%, 4.00%, 4.30%, 4.80%, 5.00%, 5.30%, 5.70%, 5.80%, 5.90%, 6.00%, 6.20%, or 6.50%, or a number within a numerical range formed with any two of the above specific values ​​as endpoints. It should be understood that in the implementation, any of the above ranges can be combined with any other range.

[0115] In some embodiments of the present invention, the Ag2O content in the strengthened layer, tensile stress layer, or core of the tempered photosensitive glass is 0.20% to 0.50%, preferably 0.20% to 0.49%, by mass percentage of oxide. In some embodiments of the present invention, the Ag2O content in the strengthened layer, tensile stress layer, or core of the tempered photosensitive glass may be 0.20%, 0.22%, 0.24%, 0.26%, 0.28%, 0.30%, 0.32%, 0.34%, 0.36%, 0.38%, 0.40%, 0.42%, 0.44%, 0.46%, 0.48%, or 0.50%, or a number within a numerical range formed with any two of the above specific values ​​as endpoints. It should be understood that in the implementation, any of the above ranges can be combined with any other range.

[0116] In some embodiments of the present invention, the mass percentage of CeO2 in the strengthened layer, tensile stress layer, or center of the strengthened photosensitive glass is 0.07% to 0.13%, preferably 0.08% to 0.12%.

[0117] In some embodiments of the present invention, the content of CeO2 in the strengthened layer, tensile stress layer, or core of the tempered photosensitive glass, by mass percentage of oxide, may be 0.07%, 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, or 0.13%, or it may be a value within a numerical range formed with any two of the above specific values ​​as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other ranges.

[0118] In this invention, Sb2O3 functions as both a weak reducing agent and a clarifying agent, and Sb 3+ Ce 4+ It undergoes an oxidation-reduction reaction with Ce 3+ Maintain the effective content of the oxide. In some embodiments of the present invention, the mass percentage of Sb2O3 in the strengthened layer, tensile stress layer, or center of the strengthened photosensitive glass is 0.20% to 0.50%, preferably 0.22% to 0.49%.

[0119] In some embodiments of the present invention, the Sb2O3 content in the strengthened layer, tensile stress layer, or core of the tempered photosensitive glass, in terms of mass percentage of oxide, may be 0.20%, 0.22%, 0.25%, 0.28%, 0.30%, 0.34%, 0.37%, 0.39%, 0.40%, 0.42%, 0.45%, 0.47%, 0.49%, or 0.50%, or it may be a value within a numerical range formed with any two of the above specific values ​​as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other range.

[0120] In the present invention, chemical strengthening can be carried out by conventionally known methods, for example, chemical strengthening may include one-step chemical strengthening or multi-step chemical strengthening.

[0121] In some embodiments of the present invention, the one-step chemical strengthening employs a salt bath containing NaNO3, preferably with a NaNO3 content of 30 wt% to 100 wt%, and the one-step chemical strengthening employs a mixed salt bath containing NaNO3 and KNO3, preferably with a KNO3 content of 80 wt% or more and less than 100 wt%, and a NaNO3 content greater than 0 and 20 wt% or less.

[0122] In some embodiments of the present invention, the temperature for the one-step chemical strengthening is 380°C to 480°C, and preferably the ion exchange time for the one-step chemical strengthening is 5h to 20h.

[0123] In some embodiments of the present invention, multi-stage chemical strengthening includes two-stage chemical strengthening, where the first stage of chemical strengthening employs a salt bath containing NaNO3, preferably with a NaNO3 content of 30 wt% to 100 wt%, and the second stage of chemical strengthening employs a salt bath containing KNO3, preferably with a KNO3 content of 60 wt% to 100 wt%.

[0124] In some embodiments of the present invention, the temperature of the first chemical strengthening stage is 380°C to 480°C, preferably the duration of the first chemical strengthening stage is 3h to 20h, and / or the temperature of the second chemical strengthening stage is 380°C to 480°C, preferably the duration of the second chemical strengthening stage is 5min to 30min.

[0125] In some embodiments of the present invention, before chemically strengthening the photosensitive glass, other conventional processing treatments can be performed on the photosensitive glass to obtain a photosensitive glass sample that meets the required specifications or requirements. Here, the processing treatments include one or more of the following: CNC machining, polishing, cleaning, 3D hot bending, and buffing. In addition, the present invention does not limit the dimensions of the strengthened photosensitive glass sample; for example, it may be 50 mm × 50 mm × 1.0 mm, 300 mm × 120 mm × 0.7 mm, etc.

[0126] In some embodiments of the present invention, the tempered photosensitive glass may be flat or curved.

[0127] In some embodiments of the present invention, the thickness t of the tempered photosensitive glass of the present invention is not particularly limited and may be, for example, 0.4 to 2.0 mm. In some embodiments of the present invention, the thickness t of the tempered photosensitive glass may be 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.2 mm, 1.4 mm, 1.6 mm, 1.8 mm or 2.0 mm, or a number within a numerical range formed with any two of the above specific numbers as endpoints. It should be understood that in the implementation, any of the above ranges may be combined with any other range.

[0128] In some embodiments of the present invention, the surface CS of the unexposed region of the tempered photosensitive glass is 300 MPa or higher, preferably 350 MPa or higher, and more preferably 350 MPa to 600 MPa. In some embodiments of the present invention, the surface CS of the unexposed region of the tempered photosensitive glass may be 350 MPa, 351 MPa, 395 MPa, 438 MPa, 385 MPa, 391 MPa, 398 MPa, 402 MPa, 422 MPa, 450 MPa, 480 MPa, 500 MPa, 530 MPa, 550 MPa, 580 MPa, or 600 MPa, or any value within a numerical range formed with any two of the above specific values ​​as endpoints, as long as a photosensitive glass having the properties required for the present invention can be obtained. It should be understood that in certain embodiments, any of the above ranges can be combined with any other range.

[0129] In some embodiments of the present invention, the single-rod static pressure strength of the tempered photosensitive glass is 200 N or more, preferably 200 N to 500 N, and more preferably 200 N to 490 N. In some embodiments of the present invention, the single-rod static pressure strength of the tempered curved photosensitive glass in the present invention may be 200 N, 250 N, 294 N, 361 N, 392 N, 301 N, 314 N, 375 N, 376 N, 390 N, 400 N, 450 N, 480 N, or 500 N, or a value within a numerical range formed with any two of the above specific values ​​as endpoints, as long as a photosensitive glass having the properties required for the present invention can be obtained. It should be understood that in certain embodiments, any of the above ranges can be combined with any other range.

[0130] The photosensitive glass and / or tempered photosensitive glass according to the present invention can be used in electronic devices, including, but not limited to, mobile phones, tablet computers, portable game consoles, portable digital devices (e.g., digital cameras), smart home devices, and smart wearable devices (e.g., smart bracelets, smartwatches, smart glasses), and can also be used in vehicles, airplanes, or aircraft, and in any necessary photosensitive glass device. For example, it can be used in the back cover glass of a mobile phone, the housing glass of a smartwatch, and for example, in the windshield of a vehicle, airplane, or aircraft, such as the front glass or side glass.

[0131] Exemplary, the photosensitive glass and / or tempered photosensitive glass according to the present invention may be configured to manufacture a cover glass, which may be a cover for the back of an electronic device, such as a mobile phone, or a camera protective cover. Exemplary, the photosensitive glass and / or tempered photosensitive glass having superior performance according to the present invention may be used in an electronic device. In some embodiments of the present invention, an electronic device is provided, which may be a mobile phone (as shown in Figure 3, the photosensitive glass and / or tempered photosensitive glass can be the back cover of a mobile phone), an electronic product such as a tablet computer, or a smart wearable device (as shown in Figure 4, the photosensitive glass and / or tempered photosensitive glass can be the case for the bottom of a smartwatch).

[0132] In some embodiments of the present invention, the electronic device includes a smart wearable device worn on the body, and includes a case having a top portion and a bottom portion, wherein the case at the bottom portion includes the above-described photosensitive glass and / or tempered photosensitive glass of the present invention. The bottom portion is designed to come into contact with the user's skin when worn.

[0133] In some embodiments of the present invention, as shown in Figure 3, the electronic device further includes a camera assembly 32 located inside a housing, the housing may include a camera protective cover 31, the camera protective cover 31 being provided to cover the camera assembly 32 to protect it, and the camera protective cover 31 employs the aforementioned photosensitive glass and / or tempered photosensitive glass. In some embodiments of the present invention, the camera protective cover 31 may employ the aforementioned photosensitive glass in part or entirely. In some embodiments of the present invention, the position in which the camera protective cover 31 is provided is determined according to the position in which the camera assembly 32 is provided, and may be located on the front side of the electronic device or on the rear side of the electronic device. In some embodiments of the present invention, the camera protective cover 31 may be a separate structure from the rear cover 33. In other embodiments of the present invention, the camera protective cover 31 may be an integral structure with the rear cover 33.

[0134] The technical aspects of the present invention will be described in more detail below with reference to examples. The examples of the present invention described in detail below are illustrative and are for illustrative purposes only, and should not be understood as limiting the present invention.

[0135] Example 1 (1) Each raw material was prepared according to the proportion of each component in Table 1, and the total mass of the prepared raw materials was 2000 g. 10 g of sodium chloride (NaCl), a clarifying agent, was added to the prepared raw materials, and then the mixture was mixed in a V-type mixer for 30 minutes to obtain a uniformly mixed raw material mixture. The raw material mixture was transferred to a platinum crucible at 1500°C and melted. The molten material was stirred with a platinum stirring rod for 10 hours. After that, it was stretched and shaped, and continuously drawn out into glass blocks of the desired specifications. The glass blocks were quickly placed in an annealing furnace at 500°C and kept warm for 10 hours, after which they were allowed to cool naturally to room temperature to obtain the base glass blocks. After sequentially performing cold working processes on the above-mentioned base glass block—cutting, CNC machining (using the RCG500S model of the CNC equipment used in this invention), and polishing—a base glass with dimensions of 50mm x 50mm x 1.0mm can be manufactured.

[0136] (2) The substrate glass obtained above was washed with ultrasound for 10 minutes, and then dried in a drying box. After cleaning, masking ink was applied to localized areas of the substrate glass, as shown in Figure 1, where the black areas are the masked areas. Subsequently, the substrate was irradiated for a total of 25 minutes under parallel ultraviolet light at a wavelength of 310 nm (UVHX800*850 pull-out type), with an ultraviolet irradiation intensity of 120 mW / cm². 2 That was the case. After UV irradiation, the glass was heat-treated according to the heat treatment process in Table 1 to obtain photosensitive glass. The heat treatment included nucleation and crystallization, with a heating rate of 10°C / min for both processes. After sequentially performing cold working processes such as laser cutting, cleavage, polishing, and chamfering on the photosensitive glass, a photosensitive glass with dimensions of φ30*1.0mm, as shown in Figure 2, was obtained.

[0137] Examples 2 to 8 Examples 1 to 8 were carried out with reference to Example 1, except that the raw material composition ratios and heat treatment process parameters differed. Relevant performance measurements were performed on Examples 1 to 8, and the results are shown in Table 1.

[0138] [Table 1]

[0139] The photosensitive glass of Examples 1, 3, and 6 was subjected to chemical strengthening treatment, which was carried out in the following order: chemical strengthening was performed for 18 hours in a 100 wt% NaNO3 salt bath at 460°C, and then chemical strengthening was performed for 20 minutes in a 100 wt% KNO3 salt bath at 440°C to obtain strengthened photosensitive glass.

[0140] The mass percentages of each component of the raw materials for the photosensitive glass in Examples 1, 3, and 6, converted to oxides, are shown in Table 2. The surface CS and single rod static pressure strength of the non-exposed region of the tempered photosensitive glass were measured, and the results are shown in Table 3.

[0141] [Table 2]

[0142] [Table 3]

[0143] Examples 9-10 and Comparative Examples 1-3 were carried out with reference to Example 1, except that the raw material compositions for Examples 9-10 and Comparative Examples 1-3 were as shown in Table 4.

[0144] Here, Examples 9-10 and Comparative Examples 1-3 are all shown based on the molar percentage of the oxide, and the same oxide was provided using different raw materials. Taking the Sb2O3 column as an example, in Examples 9-10 and Comparative Examples 1-3, the Sb2O3 content in terms of molar percentage of the oxide was 0.37 in all cases, but the difference was that in Example 9, Sb2O3 was provided using sodium antimonate as the raw material, in Example 10, Sb2O3 was provided using ammonium antimonate as the raw material, and in Comparative Examples 1-3, Sb2O3 was provided using antimony oxide (Sb2O3) as the raw material. Furthermore, when the molar percentages of oxides in Examples 9 and 10 are converted to the mass ratio of the raw material components, they are 57.96 wt% silica sand, 18.34 wt% lithium carbonate, 8.89 wt% aluminum hydroxide, 5.30 wt% potassium nitrate, 5.05 wt% sodium nitrate, 3.62 wt% zirconium oxide, 0.43 wt% silver nitrate, 0.07 wt% cerium oxide, and pentavalent antimony salt. Here, the content of pentavalent antimony salt is 0.34 wt% relative to sodium antimonate, which is within the mass ratio range of the present invention.

[0145] The Ag / Ag2O concentration (converted to the mass ratio of Ag2O) and the transmittance T3 (850 nm) of the exposure region of the photosensitive glass produced in Examples 9-10 and Comparative Examples 1-3 were measured. Furthermore, the shielding diagrams within the visible light range of the exposure region of the photosensitive glass produced in Examples 9-10 and Comparative Examples 1-3 are shown in Figure 6, and the results are shown in Table 5.

[0146] [Table 4]

[0147] [Table 5]

[0148] Photographs of the crucible bottoms after melting for Examples 9-10 and Comparative Examples 1-2 are shown in Figure 5. Here, Figure 5a is a photograph of the crucible bottom of Comparative Example 1, Figure 5b is a photograph of the crucible bottom of Comparative Example 2, Figure 5c is a photograph of the crucible bottom of Example 9, and Figure 5d is a photograph of the crucible bottom of Example 10.

[0149] Figure 6 shows actual diagrams of the shielding in the visible light range of the exposure area in Examples 9-10 and Comparative Examples 1-3 of the present invention, where red light is transmitted through the bright spots in Comparative Examples 1-3.

[0150] As can be seen from Table 1, Figures 5 and 6 above, the photosensitive glass manufactured according to the present invention ensures the stability of the glass components during the melting process of Ag-containing photosensitive glass, prevents Ag from precipitation and corroding precious metal containers, and the exposure area of ​​the manufactured photosensitive glass can achieve shielding of optical signals within the visible light and near-infrared wavelength range.

[0151] As can be seen from Table 4 and Figure 5 above, when the molar ratio of oxides is the same, if photosensitive glass is manufactured without using nitrate raw materials, corrosion of the platinum crucible is severe. Adding some nitrate raw materials can reduce the corrosion, but if silver oxide is used directly as a raw material, some corrosion of the platinum crucible occurs. Furthermore, the raw materials of the present invention can be guaranteed not to corrode the platinum crucible when sodium nitrate, potassium nitrate, silver nitrate, and sodium antimonate are used simultaneously.

[0152] As can be seen from Table 5 above, in Examples 9 and 10, Ag was used in the melt molding process of the raw materials. + There was no loss, and comparative examples 1-3 were Ag + There is a loss of Ag during melting. This is because in Examples 9-10, sodium nitrate, potassium nitrate, silver nitrate, and antimonate (sodium antimonate or ammonium antimonate) were used simultaneously as raw material components to produce photosensitive glass, resulting in a loss of Ag during melting. + It does not convert to Ag and precipitate, and the Ag2O content in the final product is almost the same as the Ag2O content in the initial composition. In contrast, in Comparative Examples 1-3, Ag was converted to Ag at the start of melting. + Because a portion of it was converted to Ag and precipitated, the Ag2O content in the final product is much lower than the Ag2O content in the initial composition. Furthermore, the exposed region of the photosensitive glass produced in Examples 9-10 has good shielding properties in the visible light region, while the exposed region of the photosensitive glass produced in Comparative Examples 1-3 transmits red light in the visible light region, and the exposed region of the photosensitive glass produced in Examples 9-10 has low transmittance at 850 nm and good shielding properties.

[0153] The above are merely preferred embodiments of the present invention and do not limit it. Those skilled in the art can make various modifications and changes to the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the scope of the spirit and principles of the present invention are all covered by the protection of the present invention. [Industrial applicability]

[0154] As described above, the present invention not only ensures the stability of the glass components during the melting process of Ag2O-containing photosensitive glass, but also generates silver atoms Ag from the decomposition of Ag2O. 0 The objective is to solve the problem of wear and tear and breakage of precious metal containers, and furthermore, to provide photosensitive glass that, when obtained after subsequent radiation treatment and heat treatment, has extremely low optical transmittance in the visible light and near-infrared wavelength range of the exposed area, thereby achieving shielding against optical signals. [Explanation of Symbols]

[0155] 11-translucent area; 12-shading area; 21. Exposure area; 22 - Unexposed area; 31 - Camera protective cover; 32-Camera assembly; 33 - Back cover; 41. Case at the bottom of the smartwatch

Claims

1. A method for manufacturing photosensitive glass, wherein the manufacturing method is: Each component of the raw material was prepared, and the components of the raw material, expressed by mass content, were as follows: 50 wt% to 60 wt% silica sand, 15 wt% to 22 wt% lithium carbonate, 6 wt% to 10 wt% aluminum hydroxide, 3 wt% to 6 wt% potassium nitrate, 3 wt% to 6 wt% sodium nitrate, 3 wt% to 5 wt% zirconium oxide, 0.3 wt% to 0.6 wt% silver nitrate, 0.05 wt% to 0.10 wt% cerium oxide, Contains pentavalent antimony salt, Based on sodium antimonate, the mass percentage of the pentavalent antimony salt in the composition of the photosensitive glass is 0.3 wt% to 0.8 wt%. Subsequently, the mixture is mixed and melted in a precious metal container, then molded, and then subjected to an annealing process to obtain a base glass. The substrate glass includes a first region and a second region, and the first region is subjected to a masking treatment, while the second region is not subjected to a masking treatment, thereby obtaining the substrate glass after masking. This includes performing radiation treatment and heat treatment on a masked substrate glass to obtain a photosensitive glass having unexposed and exposed regions, A manufacturing method characterized in that the non-exposed region corresponds to the first region, and the exposed region corresponds to the second region.

2. The components of the raw material, by mass content, include the following components: The silica sand content is 53 wt% to 59 wt%, and / or The lithium carbonate content is 17 wt% to 20 wt%, and / or The aluminum hydroxide content is 8 wt% to 10 wt%, and / or The potassium nitrate content is 4 wt% to 6 wt%, and / or The sodium nitrate content is 3.5 wt% to 5.5 wt%, and / or The zirconium oxide content is 3 wt% to 5 wt%, and / or The silver nitrate content is 0.3 wt% to 0.5 wt%, and / or The cerium oxide content is 0.05 wt% to 0.10 wt%, and / or The content of the pentavalent antimony salt is 0.3 wt% to 0.7 wt%. The manufacturing method according to claim 1.

3. The components of the raw material, by mass content, include the following components: The silica sand content is 54.00 wt% to 58.96 wt%, and / or The lithium carbonate content is 17.43 wt% to 19.94 wt%, and / or The aluminum hydroxide content is 8.22 wt% to 9.97 wt%, and / or The potassium nitrate content is 4.07 wt% to 5.97 wt%, and / or The sodium nitrate content is 3.77 wt% to 5.45 wt%, and / or The zirconium oxide content is 3.33 wt% to 4.96 wt%, and / or The silver nitrate content is 0.32 wt% to 0.49 wt%, and / or The cerium oxide content is 0.06 wt% to 0.09 wt%, and / or The content of the pentavalent antimony salt is 0.3 wt% to 0.5 wt%. The manufacturing method according to claim 1.

4. The method for producing antimony according to claim 1, characterized in that the pentavalent antimony salt comprises at least one of NaSbO3, KSbO3, NH4SbO3, and their hydrates.

5. The manufacturing method according to claim 1, characterized in that the precious metal container is a container made of a metal containing at least one of gold, platinum, and rhodium.

6. The manufacturing method according to claim 1, characterized in that the melting temperature is 1400°C to 1650°C, the melting time is 6h to 48h, and / or the annealing temperature is 400°C to 500°C, and the annealing time is 8h to 24h.

7. The manufacturing method according to any one of claims 1 to 6, characterized in that the radiation treatment method includes ultraviolet irradiation treatment.

8. The manufacturing method according to claim 7, characterized in that the wavelength of the ultraviolet irradiation treatment is 300 nm to 320 nm, the intensity of the ultraviolet irradiation treatment is 20 mW / cm² to 360 mW / cm², and the duration of the ultraviolet irradiation treatment is 5 min to 60 min.

9. The manufacturing method according to any one of claims 1 to 6, characterized in that the heat treatment includes nucleation and crystallization.

10. The heating rate of the nucleation process is 1°C / min to 10°C / min, and / or The temperature of the nucleation process is 430°C to 540°C, and / or The duration of the nucleation process is 30 min to 360 min, and / or The heating rate of the crystallization treatment is 1°C / min to 10°C / min, and / or The temperature of the crystallization treatment is 540°C to 800°C, and / or The manufacturing method according to claim 9, characterized in that the time for the crystallization treatment is 30 min to 240 min.

Citation Information

Patent Citations

  • Preparation method of photosensitive glass ceramic shell

    CN106892563A

  • Lithium-aluminum silicon-series glass material allowing photolithography, and preparation method and application thereof

    CN110937805A

  • Li-Al-Si photosensitive glass and preparation method thereof

    CN111718120A

  • Glass ceramic and glass ceramic product

    CN118388139A

  • Sensitized, photo-sensitive glass and its production

    US20180093918A1